PENDIDIKAN ISLAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Suharyat, Yayat; Agustina , Agustina; Yuliasih, Muzayyanah (Program Studi PGMI, 2018)
This research is motivated by the condition of Islamic Education as an important subject in the formation of noble values of students. Islam as a religion which is a system of belief and belief greatly influences actualization in the context of education. Formulation of the proposed problem is: